(untitled) (Ameghiniana, 2013)
Remains of two anurans from new localities of the Upper Miocene of Rio Negro (Patagonia), are described. The author assigns Wawelia ·gerholdi .n; gen.· n. sp., to the family Ceratophrydidae, and remarks its phylogenetic interest as a probable ancestor of Ceratophrys. Concerning Gigantobatrachus pm:odiiCasarn., the author descri)les some new ·skeletal remains from different individuals. The generic validity and the character of being the largest known anuran up to now, are confirmed.